And one more thing before you go-- - Shriver, Maria (New York Free Press, 2005)
A mother's advice to her daughter as she sets out on her own, expanded from a speech Shriver gave at a high school graduation.
Fear can be your best teacher -- Be willing to let go of your plan -- Learn from your mistakes -- You'll need a lot of courage -- And when you need courage ... think of the women in your life -- It's a balancing act -- Have a little gratitude -- Keep a childlike quality -- Forget your mirrors -- Don't worry about us. We'll just sit here in the dark all alone.
Keywords: Young women -- Conduct of life; Young women -- Psychology